The Improvement of Photocatalysis H2 Evolution Over g-C3N4 With Na and Cyano-Group Co-modification - Liu, Gang; Yan, Song; Shi, Lei; Yao, Lizhu (Frontiers in Chemistry, 2019)
Na and cyano-group co-modified g-C3N4 was easily synthesized and its physicochemical property was completely analyzed. The results manifested that Na and cyano-group modification could heighten visible light absorbed ability and accelerate photoinduced charge separation. When resulted Na and cyano-group co-modified g-C3N4 was splitting water H2 evolution, its H2 evolution rate was obviously improved. Furthermore, it also kept excellent stable capacity of H2 evolution and stability of chemical structure. Hence, this present study does only develop an efficient strategy to boost photocatalytic property of g-C3N4 based catalysts, but also provides useful guidance for designing more photocatalysts.